Use Of Sentinel-2 Image Vegetation Index For Biomass Growth Analysis Of Corn Plants At Various Planting Distances - Mayo Elsa, Destriana; Haerani; Ahmad Munir (Program Studi Teknik Pertanian Universitas Hasanuddin, 2023)
Biomass growth can affect the increase of corn crop production. Efforts can be made to produce good biomass growth, one of which is by adjusting plant spacing to ensure even distribution of nutrients to plants. Vegetation indices on sentinel-2 satellite imagery could used to observe the growth of corn plant biomass. The purpose of this study was to determine the relationship between sentinel-2 image vegetation index and corn plant growth parameters at a spacing of 70 x 40 cm, 70 x 20 cm and irregular. This research was conducted through several stages, i.e. (1) field data collection of plant height, biomass and leaf area, (2) downloading sentinel-2 image data for the period of December 10, 2022 - February 28, 2023, (3) atmospheric correction and image cropping, (4) transformation of NDVI and EVI vegetation indices and (5) data analysis using simple linear regression analysis to observe the relationship of NDVI and EVI vegetation indices to corn plant growth parameters. The parameters observed were plant height, biomass and leaf area. Based on growth parameters, planting distance of 70 x 40 cm produced good crop growth. Furthermore, growth parameters and vegetation index values of both NDVI and EVI showed a strong correlations at a spacing of 70 x 40 cm. In addition, the transformation map of the two indicices showed that NDVI vegetation index is categorised in the group of medium greenness, while EVI vegetation index is categorised in the group of high greenes. Based on the research results, NDVI and EVI vegetation indices had a strong relationship with the growth parameters of corn plants at a spacing of 70 x 40 cm. In other hand, spacing of 70 x 20 cm and irregular were categorised as moderate. It is found that corn plant growth parameters (plant height, biomass and leaf area) can be monitored using sentinel-2 satellite imagery.